Spirit/Religion and Ethics in African Economies - Asamoah-Gyadu, J. Kwabena (The Palgrave Handbook of African Social Ethics, 2020)
In African life and thought, sacred and secular realities are not easily separated from each other. The fusion of the two means that in most things African, but especially in African ethics and moral behavior, there is much that is inspired by religious beliefs and practices. Religion itself refers to the ways in which the physical/seen realms of existence interact with the spiritual/unseen realms. With its sense of finitude, that which is visible, in terms of human reality and existence, depends on the infinite invisible realm for power and sustenance. These ways of living out the power of the spiritual and its bearing on the physical are evident in how Africans relate to nature and eke out a living. That is not all. The inseparability between the sacred and secular is also present in such contemporary forms of religious expression as the new Pentecostal faith with its emphasis on material prosperity as prime indicators of God’s favor. Hard and the prudent use of resources are obviously critical to human flourishing, but in the new Pentecostal forms of religious expression, the faithful fulfillment of tithing obligations, for example, is key to the attraction of divine favor upon human activity. In other words, in both traditional African cultures and contemporary religion, the supernatural looms large in human affairs and also determines how people behave.
paid